دراسة تحليلية لتأثير أنواع هجوم التشويش على أداء شبكات Ad Hoc - معلا, بشرى; الرضوان, هيثم; محفوض, علاء (Latakia University Journal -Engineering Sciences Series, 2019)
Ad hoc networks are defined as decentralized, self-organization networks that contract with each other without an infrastructure. The applications of these networks in civil and military fields, wireless sensors and intelligent transport systems range to future applications of Internet of Things. These networks suffer from several challenges because of the open environment and lack of infrastructure. Attacks on the network are one of the most serious challenges facing these networks, including the jamming attack that makes the network unavailable to users in the network. In this paper we present an analytical study of the effect of the jamming attack in Ad hoc networks of various types. To achieve this goal we used the NS 3.11 simulator with the use of additions to support jamming in wireless networks. We have built simulation scenarios that include real-time traffic with different types of jamming. The simulation results showed the impact of the attack on the network performance, where as the result the packet delivery ratio decreased and the delay increased. تعرف شبكات Ad hoc على أنها شبكات لا مركزية, ذاتية التنظيم, تتصل العقد مع بعضها البعض دون وجود بنية تحتية. تتنوع تطبيقات هذه الشبكات في المجالات المدنية والعسكرية والحساسات اللاسلكية وأنظمة النقل الذكي وصولاً إلى التطبيقات المستقبلية لإنترنت الأشياء. تعاني هذه الشبكات من عدة تحديات بسبب البيئة المفتوحة وعدم وجود البنية التحتية. تعد الهجمات على الشبكة من أخطر التحديات التي تواجه هذه الشبكات, ومنها هجوم التشويش الذي يجعل الشبكة غير متاحة للمستخدمين في الشبكة. نقدم فـي هذا الـبحث دراسة تحليلية لتأثير هجوم التشويش في شبكات Ad hocبأنواعه المختلفة. استخدمنا لتحقيق هذا الغرض المحاكي NS 3.11 مع استخدام إضافاتلدعم التشويش في الشبكات اللاسلكية. قمنا ببناء سيناريوهات المحاكاة التي تتضمن حالة التشويش على إرسال حقيقي باستخدام أنواع التشويش المختلفة. وقد بينت نتائج المحاكاة تأثير الهجوم على أداء الشبكة حيث ينخفض معدل الرزم المستلمة ويزداد التأخير.